The Political Impact of Grants on Inter-Regional Relations: A Case Study of Grant Allocation from Bojonegoro to Lamongan, and Its Implications for Regional Cooperation - Asmi Rusmanayanti; Aviola Dheya Elzananda (PT Pro Panoramic Solution, 2025)
This study analyzes the political impact of the allocation of grant funds from the Bojonegoro Regency Government to the Lamongan Regency Government, as well as its implications on inter- regional relations and regional cooperation. The main focus of this study is to understand the dynamics of power, political interests, and socio-economic factors that affect the effectiveness of such cooperation. Using qualitative approaches and case study methods, data was collected through in-depth interviews with stakeholders as well as analysis of policy documents, financial statements, and media reports. The theoretical framework used is Resource Interdependence and Rational Choice Theory. The findings of the study show that the allocation of grant funds can strengthen the relationship between the regions, increase the political legitimacy of Bojonegoro, but also cause political jealousy in Lamongan, and increase the dependence of the region. Transparency and accountability in the management of grant funds are important factors in the success of the cooperation. Overall, for grants to deliver optimal benefits, transparent, accountable, and participatory mechanisms are needed, as well as a clear understanding of shared goals. The theory of resource interdependence and rational choice helps explain how political and economic interests influence cooperation decisions between regions